Reimagining Global Education Policy Research - Nishimura-Sahi, Oshie (Nordic Journal of Comparative and International Education (NJCIE), 2024)
In Finland, doctoral candidates are required to give an introductory lecture as part of their public dissertation defense. This lecture provides the audience with background information on the phenomenon studied in the dissertation, discusses the main results and central arguments, and proposes the potential contributions of the research. This paper is based on the author’s dissertation, entitled ‘Reimagining Global Education Policy Research: The Case of the European Language Framework (CEFR) Transfer to Japan’ (Nishimura-Sahi, 2024; 2020; 2022; Nishimura-Sahi & Piattoeva, 2024).